Cocksfoot and lucerne productivity in a Pinus radiata silvopastoral system: a grazed comparison - Peri, Pablo Luis (2001)
Plant and animal production from cocksfoot pasture and lucerne under 10-11 year-old radiata pine trees (200 stems/ha) and from adjacent open pastures (without trees) were measured from the Lincoln University Silvopastoral Experiment. Light intensity under trees was 50-60% of the open pasture. Liveweight gain (LWG) from lucerne was 220 g/hd/d in the open and 158 g/hd/d under trees. On cocksfoot, LWG was 132 g/hd/d in the open and 100 g/hd/d under trees. When converted to LWG/ha, lamb production from open pastures was double that from shaded pastures for lucerne (5.1 and 2.5 kg/ha/d) and cocksfoot (3.4 and 1.7 kg/ha/ d). Lucerne produced 11.2 t DM/ha in the open and 7.9 t DM/ha under trees which was 58% and 76% more than cocksfoot in the open and under trees, respectively. However, from September to November, when soil moisture was non-limiting, the lucerne DM production was 36% lower under tree shade than in the open. In comparison, the reduction was only 20% for cocksfoot, which confirms its greater 'shade tolerance'. The reduced lamb LWG produced from lambs on shaded pastures was attributed to the reduced pre-grazing pasture mass and pasture bulk density, leading to reduced apparent intakes. Crude protein and digestibility values were not influenced by shade, and clover content in cocksfoot pastures were low (<7%). It was concluded that: i) shaded pastures in silvopastoral systems limited animal production compared with open pastures owing to lower DM production rates which lowered pre-grazing pasture mass and reduced bulk density from the etiolated pasture; ii) the suitability of species for silvopastoral systems should be assessed from total plant and animal production and species persistence rather than 'shade tolerance', which only examines the relative decline in DM production under shade compared with unshaded situations. Keywords: cocksfoot, Dactylis glomerata, lamb liveweight gain, lucerne, Medicago sativa, pasture production, Pinus radiata, shade tolerance, silvopastoralism.